ANALYSIS OF RELATIONSHIP BETWEEN JOB PERFORMANCE AND JOB SATISFACTION USING SOFTWARE LISREL 7.31: A STUDY CASE AT CARREFOUR AMBASADOR BRANCH - Amran, Tiena G.; Setyowati, Rury (Industrial and Systems Engineering Assessment Journal (INASEA), 2012)
Examining the relationship between factors that effects job performance and job satisfaction is theÂ purpose of this study. Based on the extant literature and research done before on job performance and jobÂ satisfaction, we proposed a structural model depicting hypothesized associations between incentive,Â superiors and working condition on job performance and satisfaction. Data are collected from 100 floorÂ employees of Carrefour Ambasador Jakarta, through research questioner instrument, and is run withÂ LISREL 7.31 software. The results, based on structural equation modeling (SEM), showes that onlyÂ âsuperiorsâ that really effects 35.32% of job performance at Carrefour Ambasador. While job performanceÂ effects 38.75% of job satisfaction. Modification model which is the result of this study, has breaks severalÂ hypothetical assumptions that effect job satisfaction at Carrefour Ambasador.